2005
DOI: 10.1038/sj.emboj.7600748
|View full text |Cite
|
Sign up to set email alerts
|

TAF4 inactivation in embryonic fibroblasts activates TGFβ signalling and autocrine growth

Abstract: We have inactivated transcription factor TFIID subunit TBP-associated factor 4 (TAF4) in mouse embryonic fibroblasts. Mutant taf4 À/À cells are viable and contain intact TFIID comprising the related TAF4b showing that TAF4 is not an essential protein. TAF4 inactivation deregulates more than 1000 genes indicating that TFIID complexes containing TAF4 and TAF4b have distinct target gene specificities. However, taf4 À/À cell lines have altered morphology and exhibit serum-independent autocrine growth correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(98 citation statements)
references
References 42 publications
9
88
1
Order By: Relevance
“…TAF4 was then inactivated in these cells by expression of the Cre recombinase. 43 In contrast to what has been observed with other TAFs in proliferating cell lines in vitro, loss of TAF4 did not result in cell cycle arrest and apoptosis. Morover, the taf4 -/-fibroblasts contained intact TFIID.…”
Section: Taf4 a Regulator Of Growth Factor Expressioncontrasting
confidence: 44%
See 1 more Smart Citation
“…TAF4 was then inactivated in these cells by expression of the Cre recombinase. 43 In contrast to what has been observed with other TAFs in proliferating cell lines in vitro, loss of TAF4 did not result in cell cycle arrest and apoptosis. Morover, the taf4 -/-fibroblasts contained intact TFIID.…”
Section: Taf4 a Regulator Of Growth Factor Expressioncontrasting
confidence: 44%
“…43 Amongst the affected genes, are several secreted growth factors including TGFβ1, β3 and CTGF. CTGF is induced by TGFβ, has intrinsic growth factor properties and acts as a secondary mediator of the proliferative response of fibroblasts to TGFβ, in particular during the development of fibrosis.…”
Section: Taf4 a Regulator Of Growth Factor Expressionmentioning
confidence: 99%
“…Our analysis, using luciferase reporter constructs transfected to colorectal cancer cells, supports that TAF4b, but not TAF4, acts as a coactivator on specific AP-1 targets. Furthermore, in our study, we observed that an intracellular reduction of TAF4b might be compensated by induced expression levels of TAF4 (Supplementary Data), reinforcing the previous assumption that TAF4 was limiting the TAF4b-containing TFIID complexes present in cells (36). Interestingly, TAF4 and TAF4b, through their competitive equilibrium in TFIID, have been shown to regulate the expression of genes involved in cell proliferation and transforming growth factor-β signaling, known to drive tumor cells to EMT transformation (41,42).…”
Section: Discussionsupporting
confidence: 68%
“…Notably, it has been shown that individual TAFs are required for the expression of only a specific subset of genes (35)(36)(37)(38), and that the TFIID, or any of its other forms, was recruited in core promoters by a direct interaction between TAFs and their genespecific activators (39). Given that TAF4b target promoter selectivity is enhanced by activators such as c-Jun and Sp-1 (12), we propose a synergistic function of the two factors, c-Jun and TAF4b, through their interaction in which TAF4b is the coactivator of AP-1 during regulation of AP-1 target genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation